Повести. Рассказы - Вересаев Викентий Викентьевич (Правда, 1988)
Экземпляры: ф-8 (ретроконверсия) / Инвентарный номер: 28073 / Цена: 2.20 / Сис.шифр: Р1 / Авт.знак: В31 / ГРНТИ: 17.82 / ББК: 84(2=411.2)^VLBC/M